Evaluation of the efficacy of two methods for direct extraction of DNA from Mycobacterium tuberculosis sputum - Ndhlovu, Victor; Mandala, Wilson; Sloan, Derek; Kamdolozi, Mercy; Caws, Maxine; Davies, Gerry (The Journal of Infection in Developing Countries, 2018)
Introduction: Whole genome sequencing (WGS) has shown superiority over other bacterial typing methods and can be used to monitor disease transmission. The long culture period hinders use of WGS as a diagnostic tool for TB. The ideal situation would be to efficiently sequence directly from clinical specimens such as sputum. Attempts to sequence directly from Mtb clinical samples have achieved very low coverage (less than 0.7X). We compared DNA extraction methods for direct extraction from Mycobacterium tuberculosis positive sputum and assessed their suitability for Single Molecule Real Time sequencing. Methodology: We evaluated the extraction efficiency of the PrimeXtract kit and an in-house CTAB method by extracting DNA from Mtb sputum. We evaluated the methods on these parameters: ease of use, efficiency (quantity and purity) and the cost per extraction. Results: The PrimeXtract kit was able to isolate 5.93 µg/mL ± 0.94, (Mean ± SEM) concentration of DNA and a yield of 0.2975 µg ± 0.04723, (Mean ± SEM). Comparatively, the CTAB method isolated 1.88 µg/mL ± 0.38 DNA and a yield of 0.09 µg ± 0.02. Both concentration and yield from the kit were significantly (p = 0.0002) higher than those from CTAB. The PrimeXtract kit had a DNA purity ratio of 1.69 ± 0.09 compared to the CTAB’s 1.73 ± 0.14 and this difference was not statistically different. Conclusion: PrimeXtract kit has a superior extraction efficiency than the CTAB method on Mtb sputum in terms of DNA yield although no significant difference by DNA purity was seen.